Evaluation on the knowledge and acceptance of irradiated foods in the food bank in Brazil - dissemination about the benefits of the technology (Research, Society and Development, 2022)
The knowledge of the benefits of food irradiation needs to break the barriers of technological centers reaching the general public and have acceptance by consumers. The objective of this study was to evaluate, through the application of a questionnaire, the knowledge and acceptance of individuals from the CEAGESP food bank, in relation to food irradiation before and after an educational intervention that informed through text and video the benefits of applied irradiation. in food. In addition, through visual sensory analysis and presentation of graphic material, the purchase intention of irradiated food was verified in the local consumers. The results show that initially 95% of the BCA population had already consumed a product with some irradiated ingredient, however only 50% declared that they would buy it. After applying all the questions and the informative text and video about food irradiation technology as a treatment, the results showed that 80% of the subjects would buy irradiated food. In this way, the information increased the acceptance of the BCA population by 30%. In addition, it was found that 80% of CEAGESP consumers who were exposed to educational material and visual sensory analysis accept and intend to buy irradiated foods. The results show that the questionnaire was an instrument for the active dissemination of knowledge and the graphic material and visual sensory analysis are ways of disseminating this technology.